2013
DOI: 10.1101/gr.155473.113
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiling in human B cells reveals immune regulatory elements and epigenetic plasticity at Alu elements during B-cell activation

Abstract: Memory is a hallmark of adaptive immunity, wherein lymphocytes mount a superior response to a previously encountered antigen. It has been speculated that epigenetic alterations in memory lymphocytes contribute to their functional distinction from their naive counterparts. However, the nature and extent of epigenetic alterations in memory compartments remain poorly characterized. Here we profile the DNA methylome and the transcriptome of B-lymphocyte subsets representing stages of the humoral immune response be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 63 publications
8
84
0
Order By: Relevance
“…17 We showed that treatment with GSK-J4 leads to a reduction in BCL6 protein levels, perhaps through inhibition of BCR signaling. Indeed, a recent study suggested that KDM6B promotes the survival of DLBCL cells.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…17 We showed that treatment with GSK-J4 leads to a reduction in BCL6 protein levels, perhaps through inhibition of BCR signaling. Indeed, a recent study suggested that KDM6B promotes the survival of DLBCL cells.…”
Section: Discussionmentioning
confidence: 86%
“…eration. 16,17 Aberrant histone methylation or demethylation can result in inappropriate transcriptional silencing, which can drive chemoresistance and malignant transformation. 18 An analysis of histone methylation in DLBCL samples suggests that aberrant methylation increases with disease aggressiveness.…”
mentioning
confidence: 99%
“…We previously observed significant loss of DNA methylation in human GCB (Lai et al, 2013; Shaknovich et al, 2011). We hypothesized that AID would be at least partly responsible for this decrease.…”
Section: Resultsmentioning
confidence: 94%
“…DNA methylation is understood to play a key role in gene imprinting, X chromosome inactivation, and regulation of gene expression specific to tissue identity, developmental stage and cell lineage (Bird, 2002; Jones and Takai, 2001). Changes in the DNA methylome mark specific stages of B cell ontogeny and play an important role in B cell lymphomagenesis (De et al, 2013; Jeong et al, 2014; Kulis et al, 2012; Lai et al, 2013; Mayle et al, 2014; Shaknovich et al, 2010; Zhang et al, 2014). The GC stage of B cell development is associated with a proliferative burst, affinity maturation of B cells with associated SHM and CSR, all of which contribute to adaptive immune response and determine antibody diversity (Klein and Dalla-Favera, 2008), but the contribution of the methylome to these processes is not clearly defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation